Go Big or Stay Home? Structural Understanding Through the Accessibility of Precedent - Stephanie Bunt (Building Technology Educators’ Society, 2025)
Use of precedents when teaching structural concepts to architecture students is one way to illustrate complex structural behavior but may not be understood in all contexts. While the internet allows for many well documented buildings across the world to be studied through photos, their structural performance may be less clear to architecture students who can benefit from experiencing a building in person. In response, this research considers how students' understanding of structural behavior compares between the study of well-documented, non-local precedents and the study of local precedents that students can visit. Through a project assigned in an architectural structures class that required the students to build a structurally functional model of an existing building, the affordances of precedents in teaching structures are considered and the level of student understanding is reported.
Keywords: architecture; structural concepts; precedent